Correction: Ultrasensitive and in situ DNA detection in various pH environments based on a microfiber with a graphene oxide linking layer. Issue 24 (6th March 2017) - Huang, Yunyun; Yu, Bo; Guo, Tuan; Guan, Bai-Ou
Abstract : Correction for 'Ultrasensitive and in situ DNA detection in various pH environments based on a microfiber with a graphene oxide linking layer' by Yunyun Huang et al., RSC Adv., 2017, 7, 13177–13183.